Effects of graded levels of dietary protein supplementation on milk yield, body weight gain, blood biochemical parameters, and gut microbiota in lactating ewes - Zhao, Xiaoqi; Ali, Sikandar; Hassan, Mohammad Farooque; Bashir, Muhammad Amjad; Ni, Xiaojun; Lv, Chunrong; Yang, Hongyuan; Danzeng, Baiji; Quan, Guobo (Frontiers in Veterinary Science, 2023)
Dietary changes modulated the composition and diversity of gut microbiota, leading to effects on the productive performance and overall health of animals. This study aimed to investigate the effects of graded levels of dietary protein on milk yield, body weight gain, blood biochemical parameters, and gut microbiota in lactating ewes. For this purpose, a total of 18 ewes were randomly divided into three treatment groups equally and each group was fed with different crude protein levels of 8.38% (S-I), 10.42% (S-m), and 13.93% (S-h). Results indicated that the weight gain of lactating ewes was improved by increasing the level of dietary crude protein. A significant (P<0.01) improvement was observed in S-m and S-h groups in comparison to the S-l group. Similarly, the per day milk production was noted higher in the S-h group as compared to the S-m and S-I groups, however, the milk protein was not influenced by increasing levels of dietary protein. Moreover, the non-significant (P>0.05) effects were observed on blood biochemical indices in response to feeding various levels of crude protein. The concentrations of albumin (ALB) and blood urea nitrogen (BUN) in sheep increase linearly as dietary protein increases within the groups. However, significant variation was noted in S-I and S-h groups in ALB concentration, whereas the concentration of BUN was significantly higher in the S-h group. The Firmicutes and Bacteroidetes were the most dominant phyla in all treatment groups. Meanwhile, the abundance of Lachnospiraceae family members decreased as the dietary level of crude protein increased. Moreover, Rikenellaceae from Bacteroidetes phyla was dominant in the S-m group, followed by Prevotellaceae. Conclusively, it was suggested that feeding with the optimum level of dietary protein improves the productive performance and health of lactating sheep by modifying the digestive tract's beneficial bacterial communities.